PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PERJUDIAN PACU ANJING BERDASARKAN KITAB UNDANG-UNDANG HUKUM PIDANA DI WILAYAH HUKUM KOTA PAYAKUMBUH - Peni Indriati; Erdianto '; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Gamble or gambling or gambling game according to the Big Indonesia Dictionary is a game with spending money as a bet. Then gambling is risking an amount of money or possessions in the game of puzzle based on coincidence, with the goal of getting a sum of money or property that is greater than the amount of money or possessions. Gambling appears due to the unstable society both in terms of religion, moral economy as well as the state of the law. Gambling is one of the diseases of society already deeply ingrained and hard enough to be eliminated despite the threat of sanctions and penalties for this act are cleary regulated in the legislation. The purpose of writing this thesis is, First,to know the rule of law against the crime of gambling legal telic dog runway at Payakumbuh. Second, to find out the cause factor dog runway tradition of switching functions became a criminal offence in the community town of Payakumbuh. Third, to find out the problems encountered in enforcing the law against the crime of gambling laws in the area dog runway at payakumbuh.From the result of the research there where three basic issues that can be inferred. First, the enforcement of the law against the crime of gambling is already carried out in accordance with the applicable legislation, but there are still some issues that cause law enforcement against criminal acts of gambling has not been fullets and optima. Second, the existence of some of the facrors which led to a tradition transformed into criminal acts,especially the factors that came from himself of the humans. Third, the existence of several problems that hinder and must be solved by law enforcement agencies in the enforcement of the law against the crime of gambling.Keyword: Law Enforcement-Gambling-Crime